2016
DOI: 10.15171/bi.2016.05
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanisms of Cucumis sativus in diabetes-related models of oxidative stress and carbonyl stress

Abstract: Introduction: Oxidative stress and carbonyl stress have essential mediatory roles in the development of diabetes and its related complications through increasing free radicals production and impairing antioxidant defense systems. Different chemical and natural compounds have been suggested for decreasing such disorders associated with diabetes. The objectives of the present study were to investigate the protective effects of Cucumis sativus (C. sativus) fruit (cucumber) in oxidative and carbonyl stress models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…The final extract contained 24 % water. These extracts were dissolved in distilled water at the desired concentrations just before use [17,18]. Total phenolic contents were found to be 43.42 ± 1.18 and 13.57 ± 0.28 mg gallic acid equivalents (GAE) per gram of ACO and AFC (mg of GAE/g of plant extract), respectively.…”
Section: Plant Materials Preparation Of the Extractsmentioning
confidence: 99%
“…The final extract contained 24 % water. These extracts were dissolved in distilled water at the desired concentrations just before use [17,18]. Total phenolic contents were found to be 43.42 ± 1.18 and 13.57 ± 0.28 mg gallic acid equivalents (GAE) per gram of ACO and AFC (mg of GAE/g of plant extract), respectively.…”
Section: Plant Materials Preparation Of the Extractsmentioning
confidence: 99%
“…Inside the organelle, the formation of hydroxyl radical can disrupt the integrity of lysosomal membranes that results in the release of proteases into the cytosol and the development of proteolysis and cell death [27]. Our results clearly demonstrated that C. moschata efficiently prevented these sub-cellular toxic events of oxidative and carbonyl stress through the inhibition of mitochondrial membrane potential collapse, lysosomal membrane permeabilization, and cellular proteolysis.…”
Section: Discussionmentioning
confidence: 61%
“…Initially, EC50 2h concentrations of 120 μM and 5 mM were chosen for CHP and glyoxal, respectively based on our previous study [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cucumber seed oil has cholesterol-lowering effect due to which it can be used in medicine for the prevention of cardiovascular diseases. The extracts of cucumber leaves, stems, fruits, and seeds are enriched with a broad spectrum of phytonutrients such as β-carotene and α-carotene, zea-xanthin, lutein, vitamins A, C and K, proteins and aminoacids, caffeic acid, glycosides, alkaloids, tannins, phytosterols, terpenoids, saponins, flavonoids, lignans, triterpenes exhibiting antioxidant, anticancer, antidiabetic, antiulcer, antimicrobial, analgesic, hypoglycemic, hypolipidemic, and cytotoxic activity [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%